Reactive changes with microfilaria in a suspected metastatic axillary lymph node on positron emission tomography–computed tomography in breast malignancy: An interesting finding - Anuja Anand; Aarti Tyagi; Shubham Jain; Pankaj Dougall (World Journal of Nuclear Medicine)
Positron emission tomography–computed tomography (PET-CT) has evolved as an important diagnostic tool in the diagnosis and management of breast carcinoma. PET/CT can help in staging as well as detecting metastases to mediastinal, axillary, and internal mammary nodes. However, PET-CT is not useful in differentiating between inflammation and malignancy.